Chirality‐Dependent Circular Photogalvanic Effect in Enantiomorphic 2D Organic–Inorganic Hybrid Perovskites. Issue 17 (23rd March 2021) - Huang, Po‐Jung; Taniguchi, Kouji; Shigefuji, Masato; Kobayashi, Takatsugu; Matsubara, Masakazu; Sasagawa, Takao; Sato, Hiroyasu; Miyasaka, Hitoshi
Abstract: The control of the optoelectronic properties of 2D organic–inorganic hybrid perovskite (2D‐OIHP) lead halides is an increasingly prevalent topic. Herein, the observation of the circular photogalvanic effect (CPGE) in new enantiomorphic 2D‐OIHP lead iodides is reported, which are synthesized as a first OIHP‐related system belonging to a chiral space group by incorporating organic chiral cations into the inorganic layers of lead iodides. The CPGE is an optoelectronic phenomenon associated with the spin–orbit coupling of heavy atoms in noncentrosymmetric systems. Owing to the CPGE, light‐helicity‐dependent steady photocurrents are generated without an external bias voltage under the irradiation of circularly polarized light. Furthermore, the sign reversal of the CPGE photocurrent depending on the chirality of the designed 2D‐OIHP lead iodides is observed. This result indicates formation of the theoretically predicted radial spin‐polarized texture in k ‐space of chiral systems owing to spin‐momentum locking. Hence, chiral 2D‐OIHP lead halides can be a promising platform for engineering opto‐spintronic functionalities. Abstract : Chirality dependence of a novel optoelectronic phenomenon, circular photogalvanic effect, is observed in a pair of 2D organic–inorganic hybrid perovskites with introduced chiral molecules. The sign reversal of zero‐bias photocurrents between enantiomers indicates the chirality‐dependent spin‐polarized bands induced by spin–orbit coupling.